ANALISI PERUBAHAN POLA KONSUMSI RUMAH TANGGA : DAMPAK PERUBAHAN HARGA BBM (STUDI KASUS KECAMATAN KEMUNING PALEMBANG) - Muhammad Said (JURNAL KOMPETITIF, 2015)
ABSTRACT This study aims to determine how the effect of the reduction in fuel subsidies or subsidized fuel price increase the consumption pattern of low-income households, medium and high in the city of Palembang. Rising fuel prices, led to declining real incomes of households that ultimately every household will adjust their consumption patterns on the type of food and non-food. Changes in consumption patterns of food to non-food indicates a decrease levels of household welfare. The method used to obtain primary data is done by simple random sampling method is sampling with every element in the population has an equal chance of being selected into the sample of primary data in the form of questionnaires were collected by in-depth interviews (depth interview) in the group of households that group of low-income households to obtain more specific information in order to answer the research problem. While secondary data mainly comes from the Central Statistics Agency (BPS) in order to complete the Primary or comparison of data obtained. Processing the data using SPSS version 17 by first testing the validity and reliability of the data used before and after the increase in fuel prices. The results showed that the low-income community was hit hard by rising fuel prices. The result is a substitution effect where there is a change in the pattern of consumption of non-food consumption into food consumption as a result of rising the fuel priceÃ‚Â Key Word: consumption patterns, consumption of food, consumption of non- food